Correction: Corrigendum: Impaired protein translation in Drosophila models for Charcot–Marie–Tooth neuropathy caused by mutant tRNA synthetases - Sven Niehues (Nature Portfolio, 2016)
Nature Communications 6: Article number: 7520 (2015); Published: 3 July 2015; Updated: 21 January 2016. The authors inadvertently omitted Sumit Jaiswal, who was originally included in the Acknowledgements section of this Article and contributed to the cloning of transgenic constructs and the balancing of transgenic flies, from the author list.